Three-dimensional characteristics of the quasi-single helical state in the KTX. (26th November 2020) - Liu, J.; Liu, H.; Mao, W.; Luo, Y.; Yang, L.; Li, Y.; Zhang, Y.; Zhang, S.; Tang, C.; Xu, Y.
Abstract: The characteristics of various quasi-single helicities (QSHs) in the Keda Torus eXperiment (KTX) are investigated in ideal magnetohydrodynamics (MHD) simulations with self-organized helical equilibria. It is found that in the core plasma region the negative magnetic shear imposes a substantial influence on the stabilization of interchange modes, which can enhance the magnetic fluctuations of the dominant single mode. The prominent reversal shear plays a critical role on the transition to the QSH phase. This paper shows that the QSH state with a toroidal field periodicity N fp = 6 is expected to stably achieve by the negative magnetic shear in the future KTX experiments. In addition, the plasma confinement effected by subdominant modes is estimated using particle drift computations in the KTX. As the amplitude of residual subdominant modes increases the radial drift is significantly enhanced, which indicates a drastic loss of ions arises from the subdominant modes with sufficient amplitudes. The result appears to agree with experimental observations in the Madison Symmetric Torus (MST) (Bonofiglo 2019 Phys. Rev. Lett. 123 055001). This work may shed a light on the transition mechanism between the multiple helicities (MH) phase and the QSH phase in reversed-field pinch (RFP) facilities. Moreover, to improve the confinement of RFP in the QSH scenario, the critical importance of subdominant mode amplitudes on the ion confinement should be greatly considered.